Climate summits and protests have a strong impact on climate change media coverage in Germany - Jakob H. Lochner; Annika Stechemesser; Leonie Wenz (Communications Earth & Environment, 2024)
Abstract Media inform the public, thereby influencing societal debates and political decisions. Despite climate change’s importance, drivers of media attention to climate change remain differently understood. Here we assess how different sociopolitical and extreme weather events affect climate change media coverage, both immediately and in the weeks following the event. To this end, we construct a data set of over 90,000 climate change articles published in nine major German newspapers over the past three decades and apply fixed effects panel regressions to control for confounders. We find that United Nations Climate Change Conferences affect coverage most strongly and most persistently. Climate protests incite climate coverage that extends well beyond the reporting on the event itself, whereas many articles on weather extremes do not mention climate change. The influence of all events has risen over time, increasing the media prominence of climate change.